Critical Evaluation of the Independent Teaching Platform in Improving Education Quality Considering Ivan Illich's 'Deschooling Society' Principles - Marianus Tapung (Publikasi Indonesia, 2024)
The integration of the Merdeka Mengajar Platform (PMM) in the Merdeka Belajar Curriculum aims to enhance the quality of education and self-development of teachers in Indonesia through an efficient online learning model. However, its utilization requires critical evaluation considering the challenges and negative impacts observed in practice. This study critically examines the use of PMM through the lens of Ivan Illich's